Ventral striatal prediction error signaling is associated with dopamine synthesis capacity and fluid intelligence. Issue 6 (17th February 2012) - Schlagenhauf, Florian; Rapp, Michael A.; Huys, Quentin J. M.; Beck, Anne; Wüstenberg, Torsten; Deserno, Lorenz; Buchholz, Hans‐Georg; Kalbitzer, Jan; Buchert, Ralph; Bauer, Michael; Kienast, Thorsten; Cumming, Paul; et al.
Abstract Fluid intelligence represents the capacity for flexible problem solving and rapid behavioral adaptation. Rewards drive flexible behavioral adaptation, in part via a teaching signal expressed as reward prediction errors in the ventral striatum, which has been associated with phasic dopamine release in animal studies. We examined a sample of 28 healthy male adults using multimodal imaging and biological parametric mapping with (1) functional magnetic resonance imaging during a reversal learning task and (2) in a subsample of 17 subjects also with positron emission tomography using 6‐[18F]fluoro‐L‐DOPA to assess dopamine synthesis capacity. Fluid intelligence was measured using a battery of nine standard neuropsychological tests. Ventral striatal BOLD correlates of reward prediction errors were positively correlated with fluid intelligence and, in the right ventral striatum, also inversely correlated with dopamine synthesis capacity (FDOPA K inapp<inline-graphic xlink:href="ark:/27927/pgg1xqhzfj2" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />). When exploring aspects of fluid intelligence, we observed that prediction error signaling correlates with complex attention and reasoning. These findings indicate that individual differences in the capacity for flexible problem solving relate to ventral striatal activation during reward‐related learning, which in turn proved to be inversely associated with ventral striatal dopamine synthesis capacity. Hum Brain Mapp, 2013. © 2012 Wiley Periodicals, Inc.